2020
DOI: 10.1128/mbio.02580-20
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Cytokine Profiles Correlate with Disease Severity and Outcome in Longitudinal Studies of Acute Hepatitis B Virus and Hepatitis D Virus Infection in Chimpanzees

Abstract: Historical studies conducted in chimpanzees gave us the opportunity to investigate the basis for the different severities of liver damage and disease outcome associated with infection with wild-type hepatitis B virus (HBV) versus a precore HBV mutant, HBV/hepatitis D virus (HDV) coinfection, and HDV superinfection. Weekly samples from 9 chimpanzees were studied for immune responses by measuring plasma levels of 29 cytokines in parallel with alanine aminotransferase (ALT) levels and viral kinetics. Comparison o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Studies have shown that IFN-γ and IL-4, as the main cytokines of Th1 and Th2, play a key role in the balance of Th1/Th2. Th1 cells and cytokines are dominant, tend to occur HBV clearance, Th2 cells and cytokines are dominant, and tend to have persistent chronic HBV infection [40][41][42]. The level of IFN-γ was higher in OBI patients, which resulted in HBsAg and viral clearance and low HBV DNA replication level.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that IFN-γ and IL-4, as the main cytokines of Th1 and Th2, play a key role in the balance of Th1/Th2. Th1 cells and cytokines are dominant, tend to occur HBV clearance, Th2 cells and cytokines are dominant, and tend to have persistent chronic HBV infection [40][41][42]. The level of IFN-γ was higher in OBI patients, which resulted in HBsAg and viral clearance and low HBV DNA replication level.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic markers (single nucleotide polymorphisms) have been associated with the risk of developing cirrhosis, fibrosis or HCC [ 160 ], while host miRNA regulation can indicate the development of fibrosis or HCC [ 161 , 163 ]. Additionally, certain cytokines have been observed to correlate with severity of HBV disease and clinical outcomes [ 162 , 164 , 165 , 166 , 167 ]. Finally, the phenotype and functionality of HBV-specific CD8+ T cells and NK cells have been investigated for predicting HBsAg seroclearance [ 162 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some studies have used the human liver chimeric mouse model and shown that HBV/HDV infection significantly induced ISG expression ( 38 ). Chimpanzees are the only immunocompetent animals that are naturally susceptible to HBV, and they are the main animal model for studying HBV infection ( 39 ). However, their HBV-related studies were limited because of ethical issues.…”
Section: Hbvmentioning
confidence: 99%